Infrastructure Investments in Developing Economies (The Case of Vietnam) - Dang, Giang (Springer, 2015)
This book studies critical factors affecting the efficient use of public investments in infrastructure to support trade and economic development. In striving for that goal, the study reviewed the literature on construction and economic development, international trade theories, and infrastructure development. The literature review provided an understanding of the linkages between the economy, infrastructure, and trade growth. The literature has shown a positive relationship between trade and economic development. Stimulating trade has been one of the major policies in developing countries. However, the underperformance of the infrastructure systems that links these countries with their international markets is considered one of the major concerns. Investments in infrastructure have increasingly been used to improve the infrastructure quality, thus stimulating trade and economic growth in developing countries. Nevertheless, a number of infrastructure challenges faced by developing countries remain. This raises the question about the efficiency in the use of public investments in infrastructure....